The runaway science: a bibliometric analysis of the COVID-19 scientific literature: How COVID-19 has changed academic publishing - Odone, Anna; Salvati, Stefano; Bellini , Lorenzo; Bucci, Daria; Capraro , Michele; Gaetti, Giovanni; Amerio, Andrea; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: To reflect on content, trends and quality of scientific publishing on COVID-19. In particular, to report on the systematic screening, quantitative assessment and critical appraisal of the first 10,000 scientific papers published on COVID-19 and to compare how scientific outputs matched identified research priorities and public health needs. Methods: A comprehensive research strategy was developed to systematically retrieve on a daily basis all studies published on COVID-19. From included studies we extracted: bibliometric parameters, country of studies’ implementation and study design. We assigned papers to 25 a priori defined COVID-19-related topics and we described scientific outputs in relation to countries’ academic publishing ranking, as well as COVID-19 burden. Results: 10,000 scientific articles were published on COVID-19 between 20th January and 7th May 2020, accounting for 2.3% of total scientific production over the study period. One third (33%) focused on COVID-19 clinical management, with little adherence to identified research priorities. Over sixty per cent of papers were opinion pieces not reporting original data. Papers were published on 1881 different journals but with half of scientific production included in 8% of journals. The US accounted for one fourth of total scientific production, followed by China (22.2%) and Italy (9%). Conclusions: Never before in the history of academic publishing such a great volume of research focused on a single topic, this being likely to introduce major changes in the way science is produced and communicated, at the risk of bringing it far from its ultimate aim: informing clinical and public health practice and decision making.